A Study on the Factors Influencing the Satisfaction of Online Service System on the International Research Cooperation - Noh, Younghee; Chang, Rosa (International Journal of Knowledge Content Development & Technology, 2020)
Recently, as the pandemic COVIDー19 has been spread worldwide, international research cooperation has come to the fore to overcome the crisis and develop treatments. Currently, in Korea, with the support from the Ministry of Education and the Korea Research Foundation, the International Research Cooperation Information Center operates an online service system for international research cooperation as a venue for sharing results among international research cooperation researchers and invigorating such research. However, since Korea’s performance in international research cooperation is still poor, actively pursuing measures to improve professionalism and diversity based on international cooperation is deemed necessary. Therefore, in this study, factors influencing the level of satisfaction with international research cooperation online service systems were identified, and measures to increase the satisfaction of international research cooperation online service were proposed based on the analysis results. Design of the system quality factors, accuracy and consistency of the information quality factors, and professionalism of the service quality factors were verified to have a significant effect on the satisfaction with international research cooperation online service systems. Accordingly, further strengthening the aspects of design, accuracy, consistency, and professionalism was proposed as a way to increase the satisfaction of international research cooperation online service systems. URL: http://ijkcdt.net/xml/24240/24240.pdf